The dichotomy of progress: Public perceptions of global health trends and antibiotic knowledge in Georgia - Zurab Alkhanishvili (PLOS Global Public Health, 2026)
Substantial improvements in global population health have been documented over the past century; however, public perceptions of these long-term trends may not reflect empirical evidence. Misalignment between scientific progress and public understanding can affect trust, policy compliance, and the effectiveness of health governance. A nationally representative cross-sectional survey was conducted in Georgia between May and July 2023 among adults aged 18 years and older. Data were collected through face-to-face interviews using a structured questionnaire. The survey assessed public perceptions of long-term trends in global population growth, life expectancy, and under-five child mortality, as well as knowledge regarding antibiotic effectiveness against viral infections. Descriptive analyses and chi-square tests were applied to examine response patterns across sociodemographic groups. Among 1,876 respondents, recognition of declining child mortality was high (98.0%). In contrast, substantially lower proportions correctly identified increases in global population size (36.0%) and life expectancy (18.0%). Knowledge regarding antibiotic effectiveness was limited, with 32.0% of respondents correctly indicating that antibiotics are ineffective against viral infections. Variation in correct responses was observed across age groups. The findings reveal a persistent gap between documented global health progress and public perceptions in Georgia. While highly visible health indicators appear to be better recognized, broader historical trends and clinically relevant knowledge remain poorly understood. Addressing this progress - perception gap may represent an important component of strengthening public trust and improving the effectiveness of future public health governance.